2016
DOI: 10.4236/oalib.1102723
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effect of Boko-Haram Insurgency on Means of Accessing Cowpea from North-East Nigeria to Bodija Market, Ibadan, Oyo State, Nigeria

Abstract: Boko-Haram insurgency has drastically affected the supply and distribution of agricultural produce especially Cowpea from the Northeast Nigeria to the markets in southern part of Nigeria due to unwillingness of traders to embark on journey to the troubled zone for fear of attack from the insurgency. This study investigated the perceived effect of Boko Haram on available means of getting the stock from the trouble zone to the Bodija markets Ibadan, Oyo State, Nigeria. All data were described and inferential sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It covers a total land area of about 28,454 square kilometres, with a ratio of almost 1:1 distribution of male to female population (Segun-Olasanmi and Bamire, 2010). Though a substantial amount of cowpea is produced in Oyo State, the State also has several major markets for the assembly of cowpea (transported from the major producing States in the Northern parts of the country) where buyers from within and without the State come to purchase either for consumption or sale (Adejobi and Ayinde, 2005;Aluko et al, 2016;Ayinde, 2005). As a result of this, some of the major varieties of cowpea (that is, Oloyin, Drum, Milk and Sokoto) available and sold in the markets were used in this study as samples which were shown to households for ease of identification.…”
Section: Study Areamentioning
confidence: 99%
“…It covers a total land area of about 28,454 square kilometres, with a ratio of almost 1:1 distribution of male to female population (Segun-Olasanmi and Bamire, 2010). Though a substantial amount of cowpea is produced in Oyo State, the State also has several major markets for the assembly of cowpea (transported from the major producing States in the Northern parts of the country) where buyers from within and without the State come to purchase either for consumption or sale (Adejobi and Ayinde, 2005;Aluko et al, 2016;Ayinde, 2005). As a result of this, some of the major varieties of cowpea (that is, Oloyin, Drum, Milk and Sokoto) available and sold in the markets were used in this study as samples which were shown to households for ease of identification.…”
Section: Study Areamentioning
confidence: 99%
“…However, those authors point out that a weak seed industry could hinder the adoption of improved cowpea technologies. Furthermore, Aluko et al (2016) found that the Boko Haram insurgency has drastically affected the supply and distribution of agricultural produce, especially cowpea, from northeast Nigeria to the markets in the south due to unwillingness of traders to go to the troubled zone. Given the difficulty in defining a likely rate of adoption of the new technology, we estimate an ex ante probability of adoption using the GHS 2015-2016 data.…”
Section: Expected Adoption Of the New Technologymentioning
confidence: 99%
“…The bulk of the production of cowpea is attributed to the semi-arid zones of northern Nigeria despite the increasing economic importance of the commodity in the southern states. However, the current security challenges in the Northern part of Nigeria has been identified as a major factor behind the reduction in cowpea supply to the southern part of the country (Aluko et al 2016 ). The attendant threat on food security has thus become an impetus to the need to increase production in other suitable agro-ecologies.…”
Section: Introductionmentioning
confidence: 99%